Методология определения состояния дефицита йода с использованием йодной нагрузки - А. В. Гиносян (ՀՀ ԳԱԱ հրատ.)
Մշակվել և փորձարկվել է մեզով յոդիդ անիոնի դուրսբերման կինետիկան՝ յոդային ծանրաբեռնման եղանակով որոշման մեթոդ՝ յոդի անբավարարության ախտորոշման նպատակով: Որպես ախտորոշիչ միջոց օգտագործվել է յոդդեքստրին կոմպլեքս պարունակող «Արմենիկում» (դեղապատիճներ) դեղը: A new methodology of urine iodide elimination has been developed and tested in volunteers administered with a high dosage of iodine (iodine load) to identify iodine deficiency condition. As an experimental agent “Armenicum” (capsules) containing complex compound of iodine with dextrines was used.
Keywords: Medicine; Pharmacy and materia medica